2018
DOI: 10.1542/peds.2017-1326
|View full text |Cite
|
Sign up to set email alerts
|

Astrovirus Infection and Diarrhea in 8 Countries

Abstract: Astrovirus is an overlooked cause of diarrhea among vulnerable children worldwide. With the evidence presented here, we highlight the need for future research as well as the potential for astrovirus to be a target for vaccine development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
33
4
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 38 publications
5
33
4
2
Order By: Relevance
“…In a related study, norovirus GII, rotavirus, and astrovirus exhibited the highest attributable burdens of diarrhea in the first 2 years of life (6). These studies show that HAstV is an overlooked cause of diarrhea among vulnerable children worldwide, and they highlight the need for future research as well as the importance of this virus as a target for vaccine development (5,6).…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…In a related study, norovirus GII, rotavirus, and astrovirus exhibited the highest attributable burdens of diarrhea in the first 2 years of life (6). These studies show that HAstV is an overlooked cause of diarrhea among vulnerable children worldwide, and they highlight the need for future research as well as the importance of this virus as a target for vaccine development (5,6).…”
mentioning
confidence: 89%
“…middle-income countries with high prevalence of diarrhea and undernutrition was reported (5); the prevalence of HAstV in diarrheal stools was 5.6%, and remarkably, the disease severity exceeded that of all enteropathogens tested except rotavirus. In a related study, norovirus GII, rotavirus, and astrovirus exhibited the highest attributable burdens of diarrhea in the first 2 years of life (6).…”
mentioning
confidence: 96%
“…The research was carried out in compliance with the Helsinki Declaration. astrovirus in diarrheal stools was 5.6% according to a multiple-country study [9]. As previous research revealed, that the classic human astrovirus is highly diverse and consists of eight genotypes (genotype 1-8), while genotype 1 was the most prevalent genotype globally.…”
Section: Ethical Approvalmentioning
confidence: 86%
“…Classical HAstV (serotypes 1‐8) are phylogenetically distant from novel HAstV (namely MLB and VA) with amino acid identities being as low as 23% to a maximum of 54.5% depending on the open reading frames 1. Although classical HAstV are a leading cause of viral gastroenteritis, especially in children, elderly, and immunocompromised patients,2, 3, 4 the clinical manifestations of novel HAstV have not been fully characterized 5, 6, 7, 8. The spectrum of human diseases for classical and novel HAstV is not restricted to the gastrointestinal tract: both have been reported as causal agents of central nervous system infections 1.…”
Section: Introductionmentioning
confidence: 99%